Clinical significance of intragraft miR‐122 and ‐155 expression after liver transplantation. Issue 8 (17th November 2014) - Asaoka, Tadafumi; Hernandez, Dayami; Tryphonopoulos, Panagiotis; Tekin, Akin; Garcia, Jennifer; Nishida, Seigo; Fan, Ji; Beduschi, Thiago; Vianna, Rodrigo; Ruiz, Phillip
<x xml:space="preserve">Abstract</x> Aim Recurrent hepatitis C (RHC) and acute cellular rejection (AR) remain critical problems following liver transplantation (LT) in hepatitis C virus (HCV) positive recipients because of the similar clinical features. Discrimination between these conditions can be problematic, and adjunctive biomarkers would be useful to discriminate these processes. The aim of our study was to investigate the possibility of the intragraft miR‐122 and ‐155 expression as new biomarkers after LT. Methods A total of 29 HCV positive recipients were enrolled in this study. Intragraft expressions of miR‐122 and ‐155 were studied between RHC predominant (n = 17) and AR predominant cases (n = 12) using quantitative reverse transcription polymerase chain reaction. Furthermore, we investigated the correlations between these expression levels and clinical serum parameters. Results Intragraft miR‐122 expression had a good correlation with serum alkaline phosphatase (P = 0.02), but it was not correlated with the serum HCV viral load. The expression levels of miR‐122 in the AR group were significantly higher than those in the RHC group (P = 0.0006) and, inversely, the expression levels of miR‐155 in the AR group were significantly lower than those in the RHC group (P = 0.01). Conclusion Our study emphasizes a useful pattern of miR‐122 and ‐155 as ancillary markers to discriminate AR predominant cases from RHC in HCV positive patients after LT.